Religious Moderation in Islamic Education: A Systematic Literature Review with Pedagogical Implications for Primary Education - Amri Saputra; Dini Cahyati; Nur Fadilah Ramadhany; Muqowim Muqowim (Journal of Education and Teacher Training Innovation, 2026)
This study presents a Systematic Literature Review (SLR) of 224 Scopus-indexed academic articles addressing religious moderation in the context of Islamic education. The primary problem examined is the persistent gap between the normative proclamation of wasatiyyah (Islamic moderation) as an educational ideal and its actual operationalization in pedagogical practice. The central research questions are: (1) What are the dominant thematic clusters in the existing literature on religious moderation in Islamic education? (2) What learning strategies and teacher roles have been identified as effective in internalizing moderation values? (3) What research and pedagogical gaps remain unaddressed, particularly at the primary school level? The method employed is a PRISMA-guided Systematic Literature Review (SLR), drawing on data extracted from the Scopus database using the Bibliometrix R-package and covering the publication period 2015–2026, combining bibliometric analysis with inductive-deductive thematic synthesis. This urgency is underscored by the escalating tide of religious intolerance and radicalism within Indonesia's educational institutions, which calls for systematic, evidence-based responses grounded in the existing body of research. The findings reveal five major thematic clusters: the wasatiyyah paradigm and moderation theology; tolerance and pluralism; multicultural learning strategies; teacher roles and character education; and implementation challenges. The review identifies a critical research gap at the primary education level, indicating that this educational stage remains the least explored within the literature on religious moderation in Islamic education. Drawing on evidence synthesized from the broader body of literature, this study formulates pedagogical implications for primary education, including curriculum reform in Islamic Religious Education, the adoption of dialogical and cooperative learning approaches, systematic teacher professional development incorporating moderation competencies, and the integration of digital literacy to strengthen students' resilience against extremist online narratives.